Innovation in Processing Moringa Leaf Marrow Porridge with the Addition of Soybean Extract in Efforts to Prevent Stunting - Hastuti, Arti; Ibnu Fadilah; Muhammad Agung Aprialdi (Universitas Djuanda, 2024)
The high nutritional value in Moringa leaves can be used to meet the nutritional needs in breastfeeding mothers and toddlers in growth. This study aims to evaluate the best formulation of processed innovations in the Moringa Leaves Porridge Food with the addition of soybean juice in an effort to prevent stunting. The research method used is the experimental method for determining the best formulation between Moringa leaf flour 0.64%, 1% and 3% with sensory testing and empathy maps. The results showed the effective method in manufacturing the product, namely drying the flour material with a temperature tray 600C for 8 hours, the best formulation was obtained by adding 1% (w/w) Moringa leaf flour and soybean juice as a substitute for sugar sauce in marrow porridge which has a normal texture (thick viscosity), sweetness, light green, normal aroma (a little typical of Moringa leaves), this product can be used as a functional food as an effort to tackle stunting cases in Indonesia.